The Improvement of Self-Compacting Concrete Strength with ESP-Glass Powder as a Substitute for Concrete Admixture - Imani, Rafki; Nasmirayanti, Rita; Suandi, Ramadhani; Oktavani, Devita Lira (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2025)
This study investigates the utilization of waste materials, namely glass powder and eggshell powder, as partial substitutes for fine aggregate and cement in Self-Compacting Concrete (SCC). The aim is to contribute to sustainable construction practices by reducing waste and enhancing concrete performance. Experimental analysis was conducted on SCC mixtures with varying percentages of eggshell powder (ESP) and glass powder. The results demonstrated that both materials can be effectively incorporated into SCC without compromising workability, as measured by slump flow and other tests. In terms of compressive strength, the addition of glass powder resulted in a significant increase, reaching a maximum of 56.6 MPa at a 20% substitution rate. ESP also positively influenced compressive strength, with the highest value of 48.7 MPa achieved at a 15% substitution rate. Furthermore, the study observed changes in the cracking pattern of SCC with increasing percentages of ESP and glass powder. These findings highlight the potential of waste materials to enhance the mechanical properties and sustainability of SCC, providing valuable insights for future applications in the construction industry.